Comparative evaluation of intravenous tramadol and dexmedetomidine for treatment of shivering after spinal anesthesia - Siddhanta Choudhury; Bimal Krushna Panda; Diptimayee Pradhan; Neha Padhi; Dulal Kishun Soren; Debjani Seth (Wolters Kluwer Medknow Publications, 2023)
Background: Intraoperative shivering is a common complication in neuraxial anesthesia, with an incidence of 40%-50%. Shivering is an uncomfortable experience for the patient. It has many severe effects, such as increased oxygen consumption and carbon dioxide production, causing arterial hypoxia and myocardial ischemia. It contributes to delayed wound healing and late discharge from postanesthetic care. Our study aimed at a comparative evaluation of intravenous (IV) tramadol and dexmedetomidine to treat shivering after spinal anesthesia. Materials and Methods: The present work was a randomized, prospective, double-blinded study conducted at VIMSAR, Burla. One hundred patients of the American Society of Anesthesiologists Grades I and II (18-65 years of age), posted for various surgical procedures under spinal anesthesia who developed shivering, were included. After randomization, they were grouped into two groups (50 patients each). Injection dexmedetomidine (0.5 μg/kg) in Group D and injection tramadol (1 mg/kg) in Group T were given as a slow IV bolus. Grade and time taken for the onset of shivering were recorded after the spinal anesthesia. Time for cessation of shivering after IV bolus, recurrence of shivering, response rate, hemodynamic and side effects such as bradycardia, hypotension, nausea, sedation, and vomiting were analyzed. Results: Cessation of shivering was achieved earlier in Group D (3.04±0.94) than in Group T (6.62±1.49). The response rate was 100% in both groups. Vomiting and nausea were very high in Group T (30%). Twenty percent of patients were sedated with a sedation score of 2 in Group D only. A recurrence of shivering was observed in Group T (24%), requiring a repeat dose administration. Conclusion: Both tramadol and dexmedetomidine are effective in controlling shivering, but the time taken for cessation of shivering and adverse effects observed in the case of dexmedetomidine were lesser. Dexmedetomidine also provided complete cessation of shivering.